2017
DOI: 10.7754/clin.lab.2016.161029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Three Customized MSI Panels to Improve the Detection of Microsatellite Instability in Gastric Cancer

Abstract: The increased sensitivity to detect MSI-unstable tumors with customized panels including BAT40 and D18S34 indicates that precise MSI screening to discriminate MSI-H from MSS and MSI-L may be feasible for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…II) [30,31]. A standard test for MSI, also known as the Bethesda panel, was proposed at the National Cancer Institute in 1997 but also customized panels are used which precisely indicate MSI [24,32,33]. This is a panel consisting of two mononucleotide repeats (BAT25, BAT26) and three dinucleotide repeats (D2S123, D5S346, D17S250) [22].…”
Section: Microsatellite Instability In Gastric Cancermentioning
confidence: 99%
“…II) [30,31]. A standard test for MSI, also known as the Bethesda panel, was proposed at the National Cancer Institute in 1997 but also customized panels are used which precisely indicate MSI [24,32,33]. This is a panel consisting of two mononucleotide repeats (BAT25, BAT26) and three dinucleotide repeats (D2S123, D5S346, D17S250) [22].…”
Section: Microsatellite Instability In Gastric Cancermentioning
confidence: 99%
“…However, even with FLOT, 5-year overall survival reaches only 45%. Other attempts such as the use of preoperative chemotherapy combined with postoperative chemoradiotherapy in the CRITICS trial or the addition of targeted treatment such as bevacizumab in the ST03 trial did not improve overall survival compared to existing standard treatment regimens for patients with resectable GC (59,60).…”
Section: Treatment Of Locally Advanced Gastric and Gastro-oesophagealmentioning
confidence: 91%
“…Eight (13%) studies investigated KRAS amplification in addition to KRAS mutations with contradictory results. Three studies found that the incidence of KRAS amplification varied between 5% and 9% but was higher than that of KRAS mutation in GC (between 0% and 4%) (59,68,80…”
Section: Kras Amplificationmentioning
confidence: 99%
See 2 more Smart Citations